MEANS OF PREVENTING FATIGUE IN STUDENTS DURING PHYSICAL EXERTION DURING PHYSICAL EXERTION - Asqar Shamuratov (Proximus Journal Publishing, 2024)
The article is aimed at increasing the activity of students in the classroom by holding fun moments during the lesson, as well as all kinds of outdoor games to prevent students from losing interest in the lesson due to fatigue during the lesson. Alternatively, it is noted that during the lesson, the muscles of the organs of vision and hearing, the muscles of the body, especially the spine, which are in a certain position, get tired more than the muscles of the palm. Properly selected 2-3 physical exercises for a fun minute, conducted during this period, relatively reduce fatigue, improve the attention of students, increase efficiency. Holding a fun moment during the lesson is aimed at improving health, the treatment of which, like gymnastics, prevents curvature of the bones of the spine.
Keywords: scientist; scientific; students